2015
DOI: 10.5139/ijass.2015.16.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Jet Interaction for Missile with Continuous Type Side Jet Thruster

Abstract: A continuous type side jet controller which has four nozzles with thrust control devices was considered. It is deployed to a missile for high maneuverability and fast controllability in the terminal guidance phase. However, it causes more complex aerodynamic jet interactions between the side jet and the supersonic free stream than does the conventional impulse type side jet with a small single thruster. In this paper, a numerical investigation of the jet interference effects for the missile equipped with a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Many researchers have studied the lateral jet via numerical simulation and wind tunnel tests. Kang et al [4] used numerical simulation to investigate the jet interference effects under various conditions for the missile equipped with a continuous type lateral jet thruster. Wang et al [5] studied the interaction flow fields of a supersonic lateral jet penetrating the crossflow of projectiles with different fin configurations by detached eddy simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the lateral jet via numerical simulation and wind tunnel tests. Kang et al [4] used numerical simulation to investigate the jet interference effects under various conditions for the missile equipped with a continuous type lateral jet thruster. Wang et al [5] studied the interaction flow fields of a supersonic lateral jet penetrating the crossflow of projectiles with different fin configurations by detached eddy simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics obtained by the LES with turbulent crossflow showed good agreement with the experiment and a series of mesh refinement study showed reasonable grid convergence in the predicted mean and fluctuation flow quantities. Kang et al 17 conducted numerical and experimental analysis on the jet interaction of supersonic aircraft and obtained aerodynamic database. Kwak et al 18 introduced the influence of turbulence model on flow separation using wing structure.…”
Section: Introductionmentioning
confidence: 99%
“…There are mainly two ways of the jet using for missile control. One way is to increase the maneuverability at the terminal trajectory by the reaction force generated by the jet (Kang et al, 2015;. The other way is to change the flow structure by the jet to achieve the purpose of improving the aerodynamic characteristics.…”
Section: Introductionmentioning
confidence: 99%